2005
DOI: 10.1088/0953-2048/19/1/008
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of the critical current in YBa2Cu3O7−xthin films by controlling the size and density of Y2O3nanoislands on annealed SrTiO3substrates

Abstract: We introduced high density columnar defects, as artificial pinning centres (APCs) for quantized vortices, into YBa 2 Cu 3 O 7−x (YBCO) films during the film deposition procedure. APCs were introduced perpendicular to the film surface using nanosized Y 2 O 3 islands prepared on SrTiO 3 (100) substrates by pulsed laser deposition. Varying the deposition parameters and the substrate annealing conditions allowed strong changes in the shape and density of the Y 2 O 3 islands to be induced. The best performance amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 22 publications
1
52
0
Order By: Relevance
“…Growth of YBCO on top of vacuum deposited metallic (Ag) and oxide (CeO 2 , Y 2 O 3 ) nanotemplates have evidenced an influence in the vortex pinning properties [12,13]. On the other hand, we have recently shown that surface roughness of the underlying CSD buffer layers can also improve the field dependence of J c in TFA-YBCO thin films [14].…”
Section: Interfacial Nanostructuresmentioning
confidence: 99%
“…Growth of YBCO on top of vacuum deposited metallic (Ag) and oxide (CeO 2 , Y 2 O 3 ) nanotemplates have evidenced an influence in the vortex pinning properties [12,13]. On the other hand, we have recently shown that surface roughness of the underlying CSD buffer layers can also improve the field dependence of J c in TFA-YBCO thin films [14].…”
Section: Interfacial Nanostructuresmentioning
confidence: 99%
“…Several nano-engineering techniques were recently developed to insert and control APCs and, as a consequence of this, the transport performances of YBCO and REBCO films were dramatically enhanced. Many research groups were involved in the challenge of increasing the performance of coated conductors (CC) by APCs, and a lot of papers were published on this topic so far [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Several ways of externally inducing normal regions in superconductors have been demonstrated. They include: irradiation by swift heavy ions, artificially introduced regular arrays of holes, artificially introduced nanoparticles that create columnar defects in superconducting films, or surface decoration of the substrate upon which the superconducting film is grown (Civale et al, 1991;Augieri et al, 2010;Mele et al,2006;Sparing et al, 2007). However, classic nonmagnetic pinning becomes ineffective at high temperatures making it difficult to imagine practical applications of HTS materials.…”
Section: The Use Of Afm/mfm Techniques For the Study Of Hybrid Interfmentioning
confidence: 99%